Genetic structure of forensic populations. - Morton, N E (1992)
DNA-based identification depends on the probability that two different individuals have the same phenotype, which is given by kinship theory. Together with the large and consistent body of evidence on human population structure, kinship theory provides a sound basis for forensic use of DNA markers.